ANALISIS PERUBAHAN TUTUPAN LAHAN DAS TONDANO, SULAWESI UTARA SELAMA PERIODE TAHUN 2002 DAN 2015 - Wiske Rotinsulu; Hengky Walangitan; Afandi Ahmad (Graduate School Bogor Agricultural University (SPs IPB), 2018)
Monitoring land cover change is important to be done in order to understand changing mechanism and to model impacts of the change to environment and ecosystem in different scale. Research on change detection of the Tondano watershed for the period of 1989-1999 showed that the land cover has changed due to agricultural activity and urbanization (Prenzel, et al, 2006). Land cover change of the Tondano Watershed contributed to the flooding and landslide disasters in Minahasa and Manado in the early of 2014. This research was conducted to compare land cover of the Tondano Watershed between the period of 2002 and 2015 using remote sensing data and Geographical Information System (GIS). Change detection method, post classification comparison was used to gather information on land cover change in the Tondano Watershed. Results showed that there was a significant change in the land cover within thirteen years. There was a decrease of forest, paddy field and volcano areas and an increase of agriculture, residential and water body areas. Forest has been converted to dry land agriculture; paddy field area has been converted to agriculture and residential areas. An increase of residential area was caused by conversion of agricultural and paddy field areas located nearby Manado City.